β-lactam-induced OMV release promotes polymyxin tolerance in Salmonella enterica sv. Typhi - Marchant, Pedro; Vivanco, Erika; Silva, Andrés; Nevermann, Jan; Fuentes, Ignacio; Barrera, Boris; Otero, Carolina; Calderón, Iván L.; Gil, Fernando; Fuentes, Juan A. (Frontiers in Microbiology, 2024)
The rise of multidrug-resistant bacteria is a global concern, leading to a renewed reliance on older antibiotics like polymyxins as a last resort. Polymyxins, cationic cyclic peptides synthesized nonribosomally, feature a hydrophobic acyl tail and positively charged residues. Their antimicrobial mechanism involves initial interaction with Gramnegative bacterial outer-membrane components through polar and hydrophobic interactions. Outer membrane vesicles (OMVs), nano-sized proteoliposomes secreted from the outer membrane of Gram-negative bacteria, play a crucial role in tolerating harmful molecules, including cationic peptides such as polymyxins. Existing literature has documented environmental changes' impact on modulating OMV properties in Salmonella Typhimurium. However, less information exists regarding OMV production and characteristics in Salmonella Typhi. A previous study in our laboratory showed that S. Typhi ΔmrcB, a mutant associated with penicillin-binding protein (PBP, a β-lactam antibiotic target), exhibited hypervesiculation. Consequently, this study investigated the potential impact of β-lactam antibiotics on promoting polymyxin resistance tolerance via OMVs in S. Typhi. Our results demonstrated that sub-lethal doses of β-lactams increased bacterial survival against polymyxin B in S. Typhi. This phenomenon stems from βlactam antibiotics inducing hypervesiculation of OMVs with higher affinity for polymyxin B, capturing and diminishing its biologically effective concentration. These findings suggest that β-lactam antibiotic use may inadvertently contribute to decreased polymyxin effectivity against S. Typhi or other Gram-negative bacteria, complicating the effective treatment of infections caused by these pathogens. This study emphasizes the importance of evaluating the influence of β-lactam antibiotics on the interaction between OMVs and other antimicrobial agents.